Two‐dimensional electro‐optic delayed feedback system with electrical and optical coupling. Issue 3 (1st June 2018) - Miao, Suoxia; Liu, Lingfeng
Abstract : A novel coupled electro‐optic delayed feedback chaotic system is proposed and studied here. Both electrical coupling and optical coupling are used in this model, where electrical coupling is mainly used to suppress the time‐delay signature, and optical coupling is mainly used to improve its complexity. The dynamical performances and complexity are demonstrated, and the simulation results show that the complexity of this model has been greatly improved. Moreover, the time‐delay signature cannot be recognised with a low gain, and the suppress effect will be enhanced by increasing the gain coefficient. Comparing with other recently proposed models, the authors model is competitive in security, and has potential applications in secure communication and random number generation.